Yield of Cratylia argentea (desvaux) o. Kuntze to different management strategies - Lucas-Lorenzo , Darwin Eli; Santiago-Ortega , Mario Alberto; Cadena-Villegas , Said; Calzada-Marín , Jesús Miguel; Flores Santiago, Ever del Jesus (Ecosistemas y Recursos Agropecuarios, 2025)
In the Mexican tropics, livestock farming is one of the most important economic activities, primarily sourced from native pastures; these yields vary depending on the season. For this reason, the objective of this project was to study the productive behavior of Cratylia argentea, facing different management strategies, to determine the best combinations during the northerly season in Tzucacab, Yucatán, Mexico. Six treatments were used, determined by the interaction between two heights (40 and 60 cm) and three cutting frequencies (30, 60, and 90 days). Dry matter yield (DM), shoot length (SL), basal shoot number (BSN), and leaf-stem ratio (LSR) were evaluated. Data were analyzed for variance analysis using the PROC MIXED procedure of SAS 9.4, and means were compared using the Tukey test (P = 0.05). The results showed no significant differences in the effect of height (P = 0.065) or the height × frequency interaction (P = 0.386). However, the cutting frequency (30, 60 and 90 days) allowed greater biomass accumulation as the time between pruning’s increased (P < 0.0001). The highest DM yields were obtained 90 days after uniformization pruning for both cutting heights (P < 0.05). It is concluded that the DM yield is obtained by performing a cutting frequency of 90 days without being affected by the cutting heights used in this project.